Low-Grade Endometrial Stromal Sarcoma: A Case Report of a Rare Uterine Malignancy Mimicking Degenerative Uterine Leiomyoma in a Nulliparous Woman - Hyun Kyung Lee; Weon Jang; Kyoung Min Kim; Ji Soo Song (Diagnostics)
Background and Clinical Significance: Low-grade endometrial stromal sarcoma (LGESS) is a rare uterine malignancy that causes non-specific symptoms which presents more typically in younger women compared to other uterine sarcomas. Preoperative diagnosis of myometrial LGESS is challenging, as it is frequently mistaken for a benign uterine mass, such as a degenerating leiomyoma. Despite its rarity, the imaging findings of LGESS are highly variable, complicating the diagnostic process. Characteristic findings on magnetic resonance imaging T2-weighted imaging (T2WI)—including intra-tumoral low signal intensity (SI) bands (correlating with preserved myometrial bundles separated by tumor cells on histopathology), cystic/necrotic changes, and absence of a speckled appearance—have been significantly associated with LGESS. Additionally, apparent diffusion coefficient mapping can aid in the characterization of uterine masses. Case Presentation: We present a case of LGESS initially misdiagnosed as red degeneration of a uterine leiomyoma (RDL) due to a peripheral rim showing high SI on T1-weighted imaging and low SI on T2WI, which was interpreted as a thrombosed vessel. Histopathology demonstrated necrotic tissue outlined by normal uterine tissue, corresponding to the peripheral rim. We suggest that susceptibility-weighted imaging could have aided in distinguishing between the two conditions due to its high sensitivity to blood products. Moreover, diffusion-weighted imaging revealed restriction along T2 low SI bands, with no restrictions within the bands themselves, potentially indicating a viable tumor along preserved myometrium. Conclusions: These imaging features may provide valuable insights for diagnosing LGESS and differentiating it from RDL, supporting further research on LGESS imaging characteristics.